Implementation of Handover of Infrastructure, Facilities and Public Utilities by Housing Developers to Local Government in Kebumen Regency: Implementasi Penyerahan Prasarana, Sarana Dan Utilitas Umum Oleh Developer Perumahan Kepada Pemerintah Daerah Di Kabupaten Kebumen - Zulfiyani, Afrida; Kamal, Ubaidillah (Annual Review of Legal Studies, 2024)
Regent Regulation Number 40 of 2021 concerning Procedures for Handing Over Infrastructure, Facilities and Utilities of Housing and Settlement to the Regional Government is a legal umbrella as well as a guideline for developers to carry out their obligations to hand over PSU that has been completed to the Regional Government. Since its inception in June 2021 until 2023, only 7 housing complexes have handed over their PSU to the Regional Government out of 32 housing complexes registered with the Kebumen Regency Perkim-Hub Service. Many developers have not yet handed over their PSU to the Kebumen Regency Government. This study aims to determine the implementation of Kebumen Regent Regulation Number 40 of 2021 concerning Procedures for Handing Over Infrastructure, Facilities and Utilities of Housing and Settlement to the Regional Government and law enforcement by the Kebumen Regency Government against housing developers who do not hand over PSU after construction. This study applies a qualitative approach with a juridical-empirical method. Data collection through primary, secondary and tertiary legal materials. The results of this study indicate that the implementation of Regent Regulation Number 40 of 2021 concerning Procedures for Handing Over Infrastructure, Facilities and Utilities of Housing and Settlement to the Regional Government has not been implemented optimally. Of the 7 housing complexes that have handed over PSU to the Regional Government, 3 housing complexes of PSU handover were carried out cleanly and clearly by signing the minutes and certificate of PSU handover, while the other 4 housing complexes of PSU handover were carried out through PSU acquisition by the Kebumen Regency Government. Law enforcement by the Kebumen Regency Government against developers who do not hand over their PSU after completion of construction has also not been implemented firmly and consistently because the subsystem of substance has not been fulfilled and the low legal awareness of developers about the importance of carrying out PSU handover.